The Principle of Non-Refoulement as Jus Cogens: History, Application, and Exception in International Refugee Law - Syahrin, Muhammad Alvi (Faculty of Law, Universitas Negeri Semarang, 2021)
The existence of the principle of non-refoulement is a necessity and has been institutionalized in the various international legal instruments such as conventions, declarations and in customary international law. Non-refoulement principle is a fundamental concept and considered as the backbone for the entire international refugee legal system. That principle is an international legal norm that has been recognized and affirmed by the international community in multilateral international conventions and other relevant international legal instruments. This principle is very basic in the international protection system for refugees and asylum seekers and cannot be distracted by states in international relations. International organizations also recognize and apply the principle of non-refoulement consistently. The consequence is that states, both invidually and collectively, must not violate this principle. Based on legal procedures, a country can take different actions with the obligation to implement the non-refoulement principle.